HUBUNGAN PENGETAHUAN GIZI IBU HAMIL TRIMESTER III DENGAN TAFSIRAN BERAT JANIN DI UPT PUSKESMAS BAJOE KEC. TANETE RIATTANG TIMUR KAB. BONE TAHUN 2022 - Sumarni, Sumarni; Susilawati, Susilawati; Sriwidyastuti, Sriwidyastuti (Yayasan Nusantara Hasana Berdikari, 2023)
One of the factors that influence the nutrition of pregnant women is knowledge. This study aims to determine whether there is a relationship between the nutritional knowledge of pregnant women and the estimation of fetal weight (TBJ) at the Bajaoe Health Center. This study used an analytical survey with the Accidental sampling method. So that as many as 72 people were obtained. Through the Chi-Square test, the results showed that there was a relationship between the nutritional knowledge of pregnant women in the third trimester and the estimation of fetal weight with a p-value = 0.003 (p <0.05). The final conclusion of this study is that the nutritional knowledge of pregnant women in the third trimester affects the estimation of fetal weight (TBJ) at the Bajoe Health Center. This study can be a reference for health workers to be more concerned about providing knowledge to pregnant women.